Controle dos materiais de revestimento e acabamento nos hospitais com relação ao comportamento frente ao fogo - Medeiros, Cláudia Palombini (Universidade do Vale do Rio dos Sinos, 2013)
In Civil Engineering, the reaction to fire of the materials utilized as coating, finishing, decoration and equipment brought to the interior of the edification, are characterized as factors responsible for the growth and propagation of the flames, as well as, for the development of the smoke and toxic gases. These items contribute to the advance of the fire, generating human and material losses. The article presents an analysis about the control of finishing and coating materials incorporated to edifications, directed to health establishments. The law and the difficulties to comply with it, the trial methods of valid fire in Brazil, the behavior of some fuel material in the presence of fire and the importance of this control in hospitals will be brought forward. The data was obtained through bibliographic and documentary research and has the intention to analyze the subject on the current conjuncture, presenting positive and negative points of security against fire in our country.
Keywords: Materiais; Hospitais; Fogo; Materials; Hospitals; Fire